The narrative unity of Luke-Acts ; v. 1 a literary interpretation - Tannehill, Robert C. (Philadelphia, PA Fortress, 1986)
Contents : v. 1 : The Gospel according to Luke -- v. 2 : The Acts of the Apostles.
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Luke -- Criticism, interpretation, etc; Bible. N.T. Acts -- Criticism, interpretation, etc